"Femvertising": Female empowering strategies in recent Spanish commercials - Rodríguez Pérez, María Pilar; Gutiérrez, Miren (Investigaciones Feministas (Feminist Research), 2017)
Advertising is a particularly representative case of Popular Culture. Recently, the terms Femvertising and Ad-her-tising have been coined to refer to female-targeted advertising that exhibits qualities of empowering women, feminism, female activism, or women leadership and equality. This article argues that companies producing these female-empowering advertisements show different degrees of commitment to equality, but in certain cases they intend to manipulate users for bigger profits with faux activism. However, feminist strategies in advertising have the potential to disrupt gender norms, and users have the capacity to express dissatisfaction with such tactics. The research on the Spanish market is very limited; therefore, this article will explore and compare two contemporary advertising campaigns by companies Kaiku and Desigual to reveal strategies that in certain cases show a progress in terms or the advancement to gender equality, but in other cases they reinforce inequality by the reproduction of stereotypes. A detailed analysis of the Desigual advertisement “Tú decides” illustrates the power of users to reject a pseudo-feminist campaign.
Keywords: Popular Culture; advertising; gender; feminism; stereotypes.